A Peutz – Jeghers syndrome case with iron deficiency anaemia and small bowel intussusseption - Abdullah, Hilmi (Malaysian Medical Association, 2005)
Peutz-Jeghers syndrome (PJS) is an autosomal dominant inherited syndrome characterized by mucocutaneous pigmentations, with intestinal and extraintestinal polyps. It is a precancerous syndrome. The polyps can cause anaemia, intestinal obstruction and intussusception. We present a case who first presented to us with anaemia and history of intussusseption two years ago. Subsequent Small Bowel Enteroscopy revealed multiple polyps located in the jejunum which was removed by snare polypectomy. She also had multiple pigmentations on the lips. Histopathological examination of the polyps showed hamartomatous change consistent with this syndrome. Finally, we present some surveillance recommendations for people with PJS and for those at risk for PJS. This case also illustrated the advantage of using Double Balloon Enteroscopy Method which allowed us to examine to the ileum for polyps surveillance.